Single case studies as seeds: brain models that matter - Price, A (IGI Global, 2014)
Single case studies are research studies of single participants. They explore new ideas and can suggest extensions in methods and for treatment (Yin, 1984). In this article the case study refers only to conditions observed and is limited to what was observed from these comparisons between normal function and patterns of specific conditions. This does not reflect the theory of a formal case study but rather it is an attempt to show the case study and simple computer modelling as learning tools in a complex environment. Critics of case study methodology cite small case numbers as not having grounds for establishing reliability or generalization of findings and that the intensity of exposure needed for thorough case studies could bias the research findings subtracting from researcher objectivity. Early computer models were used to simulate the function of the brain and provide partial answers. They provided insight into the understanding of complex function. In recent history, computer models and case studies have been cast aside in favor of live brain imaging and complex biochemical reactions. It is good to remember that these tools brought us to the place of knowledge we enjoy today and have enlarged diagnostic and treatment choices. They are still valuable and inexpensive methods that can impact the imaginations of neuroscientists and kindle their passions to solve the complexities of the human mind one problem at a time. Greater rigor can be easily maintained by adopting a format whereby a patient would be assessed by a fully standardized neuropsychological battery and the performance then compared to large sample of normative data. The formal study is important for generalization of findings across conditions and can be applied once normative data has been collected as a basis for comparison.